Numerical analysis on water activities at catalyst-interfaces in PEM fuel cell with phase change - Suttanarak,K. (2015)
The analysis on the activities of water inside a low temperature Proton Exchange Membrane (PEM) fuel cell during its operation is set forth in this paper. The simulation model is of two-phase (vapor/liquid), three-dimensional (3-D) covering the transport phenomena such as water source term, electro osmotic drag, water back diffusion as well as the temperature distribution. The serpentine channel design with co-flow feed is considered in this investigation. The gas humidification and other settings are deliberately set so that water condensation can occur. The formulated finite-element based PEM fuel cell model is amenable to numerical techniques, such as direct collocation discretization. The simulation results from the 3-D simulator are presented as a set of various (cut) slices in two-dimensional (2-D) space. The distributions of each term in 3-D at the triple phase boundary (TPB)-the reaction site on the catalyst surface, and at the interface between the gas diffusion layer (GDL) and the flow channel help us to identify areas where water condensation is likely and least likely to occur. The obtained information is useful for improving algorithms in the control and diagnostics software for the PEM fuel cell.